CANVA-BASED INTERACTIVE LEARNING MEDIA FOR ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Nabillah, Winna; Tanjung, Ellisa Fitri (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
This research aimed to evaluate the effectiveness of using Canva-based interactive learning media in increasing students' understanding and participation in Islamic Religious Education subjects. The research method applied was a pretest-posttest experimental design using a control group and an experimental group. During the research, students from both groups were introduced to the learning material through conventional methods at first, but the experimental group was then given access to interactive learning media based on Canva. The results of the study showed a significant increase in understanding of the material and the level of participation of students in the experimental group compared to the control group. Statistical analysis showed significant differences between pretest and posttest within the experimental group, while the control group showed more limited improvement. This increase included aspects of understanding Islamic religious concepts as well as the level of student activity in the learning process. Implications include an in-depth analysis of Canva's effectiveness as a learning medium, challenges that teachers and students may face during its implementation, and suggestions for further development. The implication of this research was that Canva can be considered an effective tool in improving the quality of Islamic Religious Education learning, integrating interactive elements that motivate students to be more involved in learning.